Pharmacokinetics of orally administered meloxicam in calves: impact of breed and castration - Andreano, Sydney (My University, 2025)
No FDA-approved treatment exists to mitigate castration pain in cattle. However, meloxicam, a long-acting and cost-effective non-steroidal anti-inflammatory drug, may be administered extralabel to help attenuate pain and inflammation associated with this procedure. Although previous studies generally support the analgesic efficacy of meloxicam in cattle, reported outcomes have been variable. This variability may, in part, reflect differences in meloxicam pharmacokinetic disposition across studies, potentially influenced by covariates such as genetics (breed and sister species) and physiological status- factors that have largely been unaccounted for in existing research. This thesis aimed to use bioequivalence criteria in the absence of defined clinical significance to (1) evaluate the effect of breed on meloxicam pharmacokinetics and (2) evaluate the impact of surgical castration on the pharmacokinetics of meloxicam when administered at the time of the procedure. A tertiary aim of this thesis was to identify statistical outliers within each breed as potential candidates for genome-wide association studies to detect mutations associated with altered meloxicam metabolism and disposition. A total of 77 bull calves (3-5 months old, 75-130 kg) from three breeds (Angus n=25, Brahman n=25, and Holstein n=27) received a single oral dose of meloxicam (1 mg/kg), followed by plasma sampling at predetermined intervals over 168 h. After a washout period of at least 14 days, 41 of the calves were administered another single oral dose of meloxicam (1 mg/kg) at the time of surgical castration, with plasma sampling repeated over 168 h. Meloxicam concentrations were quantified using a validated ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method. Noncompartmental pharmacokinetic and bioequivalence analyses revealed clear differences in meloxicam disposition across breeds and between physiological states. Brahman calves exhibited the greatest extent of absorption and the slowest elimination, with markedly elevated area under the curve (AUC) and prolonged elimination half-lives (t[subscript 1/2]) compared to Angus and Holstein calves. Holstein calves also showed increased AUC and extended t[subscript 1/2] relative to Angus. The only bioequivalent parameter among breeds was CMax between Angus and Holstein calves; however, Holsteins reached CMax earlier than both Angus and Brahman, and Brahman calves had a markedly increased CMax compared to the other breeds. Following surgical castration, AUC and CMax increased, while t[subscript 1/2] decreased compared to pre-castration values. Time to CMax (TMax) remained bioequivalent before and after castration. Additionally, attempts to identify statistical outliers using t[subscript 1/2] within each breed were successful, with a total of eighteen outliers identified (Angus n=5, Brahman n=7, Holstein n=6), evenly divided between rapid and slow metabolizers. These individuals may represent distinct metabolic phenotypes, warranting further genetic analysis to explore the metabolic and genetic factors that influence meloxicam disposition. Understanding these factors could ultimately affect its analgesic efficacy and withdrawal times. Lastly, this study reinforces the importance of evaluating drug pharmacokinetics in animals under the conditions for which they are intended, rather than in healthy animals alone, as physiological state may significantly alter drug disposition. Further research is needed to determine whether breed-based differences in meloxicam disposition translate into meaningful differences in pain mitigation, and to inform breed-specific dosing regimens and withdrawal times to optimize analgesic efficacy while ensuring food safety.
Keywords: Meloxicam; Pharmacokinetics; Cattle; Breed differences; Castration; Bioequivalence